Duplex Moiety Kidney With Ureteral Ectopia; A Case Series - Kumbhar, Vikrant V; Tiwari, Charu; Shah, Hemanshi S (Journal of Pediatric Nephrology, 2016)
Ureteral ectopia is a common condition presenting as incontinence in females and incidentally detected in males. The diagnosis requires thorough radiological investigations to delineate the anatomy and formulate the treatment. The prognosis is generally excellent. We presented a series of three cases of ureteral ectopia and discussion regarding their management. Keywords: Female; Urinary Incontinence; Ectopic Ureter; Duplex Moiety Kidney.